The Last Legacy of Roland de Vaux - Sarna, Nahum M. (The Biblical archaeology review, 1980)
To English-speaking readers, the late French scholar Roland de Vaux, is known mainly as the author of Ancient Israel: Its Life and Institutions,1 that massive, erudite, skillfully synthesized, and panoramic treatment of the various forms through which the social, political and religious life of the people of Israel found expression in Biblical times. […]